A Longitudinal Analysis of the Substance Abuse, Violence, and HIV/AIDS (SAVA) Syndemic among Women in the Criminal Justice System. Issue 1 (1st January 2019) - Jones, Abenaa Acheampong; Gerke, Travis; Striley, Catherine W.; Osborne, Vicki; Whitehead, Nicole; Cottler, Linda B.
ABSTRACT: Using data from a randomized controlled trial of 319 women mainly recruited from a Municipal Drug Court System in St. Louis, MO, this study evaluates substance use, victimization, and HIV/AIDS risk behaviors over time. The results indicated that, for all participants, the likelihood of victimization, using drugs, and meeting the criteria for HIV/AIDS risk decreased by 46% by the eight-month follow-up; however, results did not differ significantly by intervention group. Women who were sexually abused as a child, had 4+ arrests, or believed they had sexual and drug-using behaviors that need changing at baseline were more likely to experience these issues over time.